2005
DOI: 10.4269/ajtmh.2005.72.243
|View full text |Cite
|
Sign up to set email alerts
|

Difference in Susceptibility to Malaria Between Two Sympatric Ethnic Groups in Mali

Abstract: We compared malaria indicators among sympatric groups to study human heterogeneities in the response to Plasmodium falciparum malaria infection. Four cross-sectional surveys and two longitudinal surveys in two sympatric ethnic groups (Dogon and Fulani) in Mali were carried out from 1998 to 2000. Spleen and parasite rates were evaluated during the cross-sectional surveys and disease incidence was assessed during longitudinal surveys. In spite of similar sociocultural factors and entomologic inoculation rates be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

17
104
0

Year Published

2008
2008
2014
2014

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 102 publications
(121 citation statements)
references
References 21 publications
17
104
0
Order By: Relevance
“…These differences could result from non-genetic factors such as culture, nutritional status or patterns of disease transmission or incidence, but in some cases they appear to be from genetic differences such as different frequencies of resistance variants (for example, high frequency of Duffy 'null' in Africa confers resistance to P. vivax, see below; high frequency of a-thalassemia in Nepalese populations, Modiano et al, 1991), epistasis with other host resistance variants or differences in unknown genetic resistance factors (Dolo et al, 2005).…”
Section: General Backgroundmentioning
confidence: 99%
“…These differences could result from non-genetic factors such as culture, nutritional status or patterns of disease transmission or incidence, but in some cases they appear to be from genetic differences such as different frequencies of resistance variants (for example, high frequency of Duffy 'null' in Africa confers resistance to P. vivax, see below; high frequency of a-thalassemia in Nepalese populations, Modiano et al, 1991), epistasis with other host resistance variants or differences in unknown genetic resistance factors (Dolo et al, 2005).…”
Section: General Backgroundmentioning
confidence: 99%
“…Interestingly, several studies have shown that ethnically diverse African populations may differ in regard to genetic susceptibility to malarial infection. A variant in the promoter region of the IL4 gene, for example, is associated with a decrease in P. falciparum infection in the pastoralist Fulani from Mali, as evidenced by lower parasite load, but no such genetic association is observed in the neighboring agriculturalist Dogon population (52,213). Other studies also reported lower prevalence of malaria parasites and fewer clinical attacks of malaria among the Fulani compared to other ethnically distinct populations in neighboring villages (107,133, 152a).…”
Section: Malariamentioning
confidence: 78%
“…This resistance was not associated to classic malaria resistance genes (4), and the analysis of the antibody response to P. falciparum antigens revealed higher immune reactivity in Fulani than in sympatric ethnic groups (1,5,6). The hypothesis of a stronger activation of the immune system in the Fulani is also suggested by the higher frequency in this group of the tropical splenomegaly syndrome (2,7) and by the higher humoral immune response to other pathogens (Schistosoma haematobium, hepatitis B, and cytomegalovirus). (D.M., unpublished data).…”
mentioning
confidence: 80%
“…This interethnic comparative approach was applied in extensive studies performed in hyperendemic rural areas of Burkina Faso and Mali, West Africa. These studies showed obvious interethnic heterogeneities in the susceptibility to Plasmodium falciparum malaria among sympatric ethnic groups, Fulani, Mossi, Rimaibé, and Dogon (1,2), with different genetic background (3). Despite similar exposure to malaria and comparable use of protective measures, the Fulani were less parasitized and less affected by the disease.…”
mentioning
confidence: 99%